PARTISIPASI PASANGAN USIA SUBUR (PUS) DALAM PELAKANAAN PROGRAM KB DI JORONG AIR DINGIN KANAGARIAN SIMPANG TONANG KECAMATAN DUA KOTO KABUPATEN PASAMAN - Ariesman, Deddi - (Pendidikan Geografi, 2014)
The purpose of this research are to know and analyze how the participation of couples of childbearing age in the implemenlation of family planning programs in Jorong Air Dingin, Kanagarian Simpang Tonang, Kecamatan Dua Koto, Kabupaten Pasaman which is survey from knowledge fertile couple and childbirth couples of childbearing age is. The type of this research is classifiet into Qualitative research. In here, informant of the research is taken by pourposive sampling techniqve . Purposive sampling techniqve is sampling techniqve of data sovrces with particular consideration. The selection of informants was done by researchers first have to know that people are selected able to provid the desired information. The information in this study wereall couples of childbearing age in Jorong Air Dingin.The result of the research: 1). background knowledge of couples of childbearing age about KB program (family planning programs) in Jorong Air Dingin, Kanagarian Simpang Tonang, Kecamatan Dua Koto, Kabupaten Pasaman are goudenaugh, but is not good from its application. It can be seen that the couples of childbearing age in Jorong Air Dingin despite knowing family planning programs (KB), but it only a small part of couples of childbearing age who implement the family planning program (KB). Although the researcher has been done the extension on Jorong Air Dingin and couples of childbearing age have participated in the conseling of family planning programs (KB). But still a little new age of infertile couples who participate/join to be family planning programs (KB) participant. 2). The birth of a baby couples of childbearing age in Jorong Air Dingin. Influenced by several factors including, desire number of children inmarriage, to improve the offspring. Coring for when old age, and also they want to have a boy (son) and health factors.